The Snow Globe Adventure - Walker, Caroline (Great Britain Franklin Watts, 2020)
Mia and her dad have moved from their home in a warm climate, to a very, very cold one. The one thing Mia is looking forward to is seeing snow for the first time. Little does she know there will be snow and much more - including some magic!